HIGHER EDUCATION REFORM IN LITHUANIA WITH EMPHASIS ON LITHUANIAN EDUCATIONAL STRATEGY - Egle Bileviciute; Inga Zaleniene (European Scientific Journal, ESJ, 2013)
Reforms of higher education are influenced both directly and indirectly by global social, economical, cultural and demographical changes in the world and European countries. High schools open to innovations must react to the changes and challenges in their surrounding, as well as get involved into competition in the field of studies and scientific research. Contemporary trends in the process of education management in various countries and regions show that the higher education becomes crucial factor making huge influence on different regions of the world. More and more people come to understanding of modern competence and qualification necessity for innovative knowledge based economy. Development of higher education in Lithuania has been a complicated and multi-valued process very closely related to other dimensions of the Lithuanian state development – political regime and historical situation, economical and social structure of the country, ideological and cultural changes paradigms.